2020
DOI: 10.1111/all.14564
|View full text |Cite
|
Sign up to set email alerts
|

Dominant atopy risk mutations identified by mouse forward genetic analysis

Abstract: Background Atopy, the overall tendency to become sensitized to an allergen, is heritable but seldom ascribed to mutations within specific genes. Atopic individuals develop abnormally elevated IgE responses to immunization with potential allergens. To gain insight into the genetic causes of atopy, we carried out a forward genetic screen for atopy in mice. Methods We screened mice carrying homozygous and heterozygous N‐ethyl‐N‐nitrosourea (ENU)–induced germline mutations for aberrant antigen‐specific IgE and IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Therefore, the regulation of PC differentiation by PPP3R1 warrants further study, particularly given the prevalence of calcineurin inhibitors in the clinic. Furthermore, a recent forward genetic analysis in mice identified mutations in Plcg2 and Syk, which resulted in augmentation of the IgE response to papain immunization (SoRelle et al, 2020). Human mutations in PLCG2, which attenuate calcium signaling in B cells (Wang et al, 2014), also lead to enhanced allergen-specific IgE levels in the context of phospholipase-associated antibody deficiency and immune dysregulation (Milner, 2020).…”
Section: Articlementioning
confidence: 99%
“…Therefore, the regulation of PC differentiation by PPP3R1 warrants further study, particularly given the prevalence of calcineurin inhibitors in the clinic. Furthermore, a recent forward genetic analysis in mice identified mutations in Plcg2 and Syk, which resulted in augmentation of the IgE response to papain immunization (SoRelle et al, 2020). Human mutations in PLCG2, which attenuate calcium signaling in B cells (Wang et al, 2014), also lead to enhanced allergen-specific IgE levels in the context of phospholipase-associated antibody deficiency and immune dysregulation (Milner, 2020).…”
Section: Articlementioning
confidence: 99%
“…In support of this idea, a wealth of literature links elevated IgE and/or atopy with primary immunodeficiencies or mutations associated with impairments in antigen receptor signaling pathways ( Sokol and Milner, 2018 ), although aberrations of these pathways would likely affect B cells and T cells in addition to PCs. A recent mutagenesis screen in mice determined that several mutations in genes with a role in BCR signaling, including Syk and Plcg2 , led to increased IgE production ( SoRelle et al, 2021 ). This study estimated that over a third of the human population may be heterozygous carriers for atopy risk alleles that affect BCR signaling or class switch recombination.…”
Section: Discussionmentioning
confidence: 99%
“…While these mice indeed had increased frequencies of IgE B cells in GCs, unexpectedly they also had increased numbers of IgE PCs ( Haniuda et al, 2016 ; Yang et al, 2016 ). Moreover, a recent mutagenesis screen in mice found that IgE production was increased when BCR signaling was impaired ( SoRelle et al, 2021 ). One possibility is that the increases in IgE PCs in the context of in vivo BCR signaling impairments were due to the enhanced IgE GC B cell responses.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that B cell intrinsic roles contribute to the previously identified role for NFAT proteins in inhibiting IgE and IgG1 production (Peng et al, 2001), their association with autoimmunity and allergy in GWAS studies(Ferreira et al, 2017), and enhanced allergic responses associated with elevated serum IgE levels in transplant patients treated with cyclosporin A or tacrolimus, both of which inhibit calcineurin (Asante-Korang et al, 1996; Kawamura et al, 1997). Furthermore a recent forward genetic analysis in mice identified mutations in Plcg2 and Syk , which resulted in augmentation of the IgE response to papain immunization (SoRelle et al, 2020). Human mutations in PLCG2 , which attenuate calcium signaling in B cells (Wang et al, 2014) also lead to enhanced allergen-specific IgE levels in the context of phospholipase-associated antibody deficiency and immune dysregulation (Milner, 2020).…”
Section: Discussionmentioning
confidence: 99%